Effect of temperature on the mechanism of ethanol oxidation on carbon supported Pt, PtRu and Pt3Sn electrocatalysts - Colmati, F.; Antolini, E.; Gonzalez, E.R.
The electrochemical oxidation of ethanol on carbon supported Pt, PtRu and Pt3Sn catalysts was studied in acid solutions at room temperature and in direct ethanol fuel cells (DEFC)in the temperature range 70.100 .C. In all the experiments, an enhancement of the activity for the ethanol oxidation was observed on the binary catalysts. In acid solution the improvement at low current densities was higher on PtRu than on Pt3Sn. In DEFC tests, at 70 .C the cells with PtRu and Pt3Sn showed about the same performance, while for T>70.C the cells with Pt3Sn as anode material performed better than those with PtRu as anode material. The apparent activation energy for ethanol oxidation on PtRu catalyst was lower than on Pt3Sn, particularly at high cell potentials, i.e. at low current densities. At low temperatures and/or low current densities, the positive effect of Ru oxides on the bifunctional mechanism determined the enhancement of activity for the ethanol oxidation reaction, while at high temperatures the positive effect of Sn alloying (enlarged lattice parameter)on CH3CH2OH adsorption and C.C cleavage prevails.
Keywords: DIRECT ETHANOL FUEL CELL; ETHANOL OXIDATION; PTSN ALLOY; PTRU ALLOY